Morfologi Spermatozoa Manusia setelah Simpan Beku dengan Medium TES-Tris Yolk Citrat (TES-TYC) - Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The aim of this research was to evaluate the effect of semen cryopreservation using TES-Tris yolk citrat (TES-TYC) medium on morphology of the sperm. Semen fulfilling inclusion criteria with WHO criteria. The sperm vitality was counted by initial data. The semen was mixed with TES-TYC medium and cryopreserved in liquid nitrogen. After one mounth the semen was thawed and recounted its sperm morphology. The data showed that the morphology of post freezing sperm cryopreserved was not significant different compared to the morphology of pre freezing sperm. It could be concluded that morphology of human sperm could not as indicator to evaluate the effect of semen cryopreservation using TES-Tris yolk citrat (TES-TYC). Key word : Sperm Morphology, semen cryopreservation.